EFL Instructors’ Corpus Literacy and Their Perceptions of Using Corpora to Teach L2 Vocabulary - Onur, Fulya Eslek; Tosun, Sibel (Yusuf DEMİR, 2023)
Corpus literacy is "the ability to use the technology of corpus linguistics to investigate language and enhance the language development of students” (Heather & Helt, 2012, p.417). The recent literature focused primarily on the perceptions of students and teachers about corpus use in learning and teaching vocabulary or investigated corpus literacy alone, but EFL teachers' corpus literacy is not explored. This study employed an explanatory sequential mixed-method design to investigate the corpus literacy of EFL instructors and their perceptions of using corpora to teach second-language vocabulary. A total of 41 EFL instructors working in 17 different state universities in Turkiye participated in the study. Data were gathered through a questionnaire and semi-structured interviews. The results showed that the EFL instructors had low to medium levels of corpus literacy. In addition, there was no correlation between corpus literacy and the teaching experience of the participants. The results also showed that despite their familiarity with corpora, the instructors had never used one to teach vocabulary. Furthermore, the majority of the participants learned about corpora and corpus tools during their Ph.D. and MA studies in English language teaching and linguistics, mostly through coursework and publications.
Keywords: Applied Linguistics and Educational Linguistics; Uygulamalı Dilbilim ve Eğitim Dilbilimi